Driving Growth from the Ground Up - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank Group, spoke about the urgency of growth in developing countries. He discussed innovations in digital financial services that provide secure systems to allow poor people to electronically receive remittances, foreign aid, and social safety-net payments as well as their earnings. He cautioned about the slow global growth, and it's paramount that countries carry out well-designed structural reforms to ignite domestic growth. He highlighted on the importance of a clear analysis and understanding of a country's laws and regulations and a path of reforms or catalytic investments that will expand the private sector. Finally, he concluded by saying that World Bank Group won’t give up on its main goal of reducing extreme poverty.